A influência da dependência financeira na efetividade da gestão de municípios brasileiros - Lima, Caio Raoni Pereira (2023)
According to the Brazilian federative pact, local governments have great importance in providing quality goods and services to the local population, given their proximity and knowledge about the needs of residents. To do this, however, they rely on a smaller tax revenue base, given that most taxes are more efficiently collected by higher governments. In this sense, intergovernmental transfers are used as a mechanism to correct the gap between local governments revenues and expenses. However, the federalism literature reports adverse effects generated by the high financial dependence of local governments on resources of this nature. In addition to the fiscal illusion generated among residents and the increase in expenses by the manager, scientific evidence suggests that high financial dependence creates obstacles to economic development, as it reduces the local manager's capacity for action in providing goods and services to the population. On the other hand, the literature also highlights the importance of evaluating the effectiveness, efficiency and effectiveness of public management. This research highlights effectiveness as meeting the objectives set, causing the best possible impact with the actions. In this sense, this research seeks to analyze the relationship between financial dependence and effectiveness, with a view to obtaining directions that help municipal public management to obtain higher levels of effectiveness and maximize the use of public resources to meet the needs of the population. To this end, an econometric model was developed that considered effectiveness as the dependent variable, financial dependence as the independent variable and GDP per capita and population as control variables. An unbalanced panel was composed that used data from Brazilian local governments available from 2015 to 2020 and used quantile regression to analyze the influence on effectiveness quartiles. The results suggest that financial dependence has a negative relationship with effectiveness. It was also observed that local governments that have greater budgetary autonomy, collecting a higher level of their own revenue, also achieve the highest effectiveness rates. Furthermore, it was noticed that in the areas of education, health and planning, where there is greater regulation of the manager's actions, this influence is less. The results obtained suggest that increasing fiscal effort, with the effective institution and collection of municipal taxes, can improve the effectiveness of municipal management, contributing to meeting population satisfaction and promoting the country's socioeconomic development.